Biomarkers, Inflammation, and Bipolar Disorder: Association Between the Improvement of Bipolar Disorder Severity and the Improvement in C-Reactive Protein Levels After 7 Days of Inpatient Treatment - Cuomo, Alessandro; Koukouna, Despoina; Spiti, Alessandro; Barillà, Giovanni; Goracci, Arianna; Bolognesi, Simone; Fagiolini, Andrea (Frontiers in Psychiatry, 2021)
Introduction Compared to the general population, people with severe mental illness (SMI) have a poorer health status and a higher mortality rate, with a 10–20-year reduction in life expectancy. Excess mortality and morbidity in SMI have been explained by intertwined components. Inflammatory processes could increase the morbidity and mortality risk in patients with bipolar disorder (BD) because of a bidirectional interaction between BD and conditions related to inflammation. This pilot study aimed to evaluate the relationship between C-Reactive-Protein (CRP) and bipolar disorder severity. Methods A retrospective observational study was conducted on 61 hospitalized patients with bipolar disorder. CRP was measured at admission to inpatient treatment (T0) and after seven days from the admission (T1). Clinical Global Impression for Depression, Mania and Overall Bipolar Illness were recorded at T0 and T1. Comparisons among the recorded CRP values were determined through the paired t-test. Correlations between CRP and CGI scores were determined through Spearman’s correlation coefficient at T0 and T1. Results A statistically significant decrease in CRP values was observed after 7 days of hospitalization (p < 0.001) and positive significant correlations emerged between CRP and CGI scores at T0 and T1. Conclusion Patients admitted to the inpatient unit reported a statistically significant decrease of CRP values during the first seven days of treatment. Although the direction of the relationship between BP severity and inflammation status continues to remain unclear, this study showed a relationship between the improvement of bipolar disease symptoms and the improvement of the inflammatory marker CRP.